Pengaruh Current Ratio, Debt to Asset Ratio dan, Debt to Equity Ratio terhadap Return on Asset pada PT Patria Anugrah Sentosa - Gita Irma Yanti; Amiruddin Syarif (Research and Strategic Studies Center (Pusat Riset dan Kajian Strategis) Fakultas Syariah IAI Nasional Laa Roiba, 2023)
This study aims to determine the effect of Current Ratio, Debt To Asset Ratio, and Debt To Equity Ratio on return on assets at PT. Patria Anugrah Sentosa 2019-2021. The object of this research is PT. Patria Anugrah Sentosa 2019-2021. The data collection method is the documentation method, which is carried out by taking data from the 2019-2021 balance sheet which has been documented by the company PT. Patria Anugerah Sentosa. Based on the results of data analysis with the help of SPSS 25, it shows that the results of the partial hypothesis test (t-test) prove that the Current Ratio, Debt To Asset Ratio, and Debt To Equity Ratio to return on assets at PT. Patria Anugrah Sentosa 2019-2021 Keywords: Current Ratio, Debt to Asset Ratio, Debt to Equity Ratio Return on Asset.